We have to solve the system of equations:
![\begin{gathered} 2x+3y=-10 \\ 5x+2y=8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ez9m8vskswzzb9lceb8aecb3evthzx9miv.png)
We can solve it by substitution.
We find the value of x in function of y from the first equation:
![\begin{gathered} 2x+3y=-10 \\ 2x=-10-3y \\ x=(-10-3y)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hoxbg39lb6u8ffy9m69pooqeexkg3mz9ol.png)
Then, we substitute the value of x in the second equation and solve for y:
![\begin{gathered} 5x+2y=8 \\ 5((-10-3y)/(2))+2y=8 \\ -(5\cdot10)/(2)-(5\cdot3y)/(2)+2y=8 \\ -25-(15)/(2)y+2y=8 \\ (2-(15)/(2))y=8+25 \\ (4-15)/(2)y=33 \\ (-11)/(2)y=33 \\ y=(33\cdot2)/(-11) \\ y=-(66)/(11) \\ y=-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yk821wff3v8o6ztq83rk1xndv3m6bq6nmb.png)
With the value of y=-6, we can solve for x:
![x=(-10-3y)/(2)=(-10-3\cdot(-6))/(2)=(-10+18)/(2)=(8)/(2)=4](https://img.qammunity.org/2023/formulas/mathematics/college/7lpg5148o65wb6ni0mbg9muxwqxv79sp7u.png)
Answer: x=4 and y=-6